מה ההפך של y = log_4 (x-3) + 2x? ?

מה ההפך של y = log_4 (x-3) + 2x? ?
Anonim

תשובה:

#x = 1/2 (6 + W (2 ^ 2y-11)) #

הסבר:

אנו יכולים לפתור בעיה זו באמצעות מה שנקרא פונקציה Lambert #W (cdot) #

en.wikipedia.org/wiki/Lambert_W_function

#y = lnabs (x-3) / ln4 + 2x rRrr y ln4 = lnabs (x-3) + 2x ln4 #

עכשיו עושה #z = x-3 #

# e ^ (y ln4) = z e ^ (2 (z + 3) ln4) = ze ^ (2z) e ^ (6 ln4) # או

#e ^ (y-6) ln4) = z e ^ (2z) # או

# 2 e ^ (y-6) ln4) = 2z e ^ (2z) #

עכשיו באמצעות שקילות

#Y = X e ^ x rRrr X = W (Y) #

# 2z = W (2 e ^ (y-6) ln4)) rRrr z = 1/2 W (2 e ^ (y-6) ln4)) #

ולבסוף

#x = 1/2 W (2 e ^ ((y-6) ln4)) + 3 # כי ניתן לפשט

#x = 1/2 (6 + W (2 ^ (2y-11))) #